Text, Authority, and Authoritarianism: Decolonizing Uṣūl al-Fiqh through the Integration of Khaled Abou El Fadl’s Authoritative Hermeneutics into Islamic Legal Methodology - Zuhri Humaidi; Syaiful Bahri (Tribakti: Jurnal Pemikiran Keislaman, 2026)
Contemporary studies of uṣūl al-fiqh continue to encounter epistemological challenges due to interpretive models that position the relationship between texts, interpreters, and religious authority in a hierarchical manner, potentially leading to authoritarian tendencies in Islamic legal reasoning. Khaled Abou El-Fadl’s authoritative hermeneutics emerges as a critique of the monopoly of religious authority by proposing an interpretive framework that is dialogical, ethical, and accountable. However, the contribution of Abou El-Fadl’s thought to reconstructing the methodology of uṣūl al-fiqh has not been systematically examined. This article aims to analyze the concept of authoritative hermeneutics and formulate its integration into the development of contemporary uṣūl al-fiqh. Employing a qualitative library-based approach with a descriptive-analytical method, this study examines Abou El-Fadl’s works alongside classical and contemporary uṣūl al-fiqh literature through comparative-interpretative analysis. The findings reveal that authoritative hermeneutics contributes to four methodological dimensions of uṣūl al-fiqh. First, regarding Islamic legal rulings (ḥukm sharʿī), it distinguishes divine authority from human interpretation, positioning law as an ongoing interpretive process. Second, concerning legal sources and evidence (adillah), it strengthens textual verification mechanisms to prevent selective and ideological use of religious texts. Third, within legal reasoning methods (istinbāṭ), it expands interpretation by incorporating moral considerations, social contexts, and the ethical objectives of Islamic law. Fourth, regarding the qualification of mujtahid, Abou El-Fadl reformulates interpretive authority through five principles: honesty, diligence, self-restraint, comprehensiveness, and rationality. This article argues that authoritative hermeneutics does not replace the classical tradition of uṣūl al-fiqh but reconstructs its epistemological foundation toward a more inclusive, critical, and socially responsive Islamic legal methodology.